Could the Tree of Life Model Be a Useful Approach for UK Mental Health Contexts? A Review of the Literature - Parham, Sophie; Ibrahim, Jeyda; Foxwell, Kate (Narrative Works, 2021)
Some suggest the ethos of the Tree of Life (ToL) group aligns with the concept of “personal-recovery” promoted in mental health policy. Thus, it is claimed that the group could be a useful approach within UK mental health services. This review collated 14 papers to explore whether existing literature regarding the ToL group supports this assertion. The papers were synthesized using the thematic analysis method and three broad themes were identified, which support the argument for its utility within services. These were recovery-aligned themes, the inclusivity of the model, and group processes relevant to mental health contexts. The papers are critically appraised, key concerns regarding the wider literature discussed, and clinical implications summarized.